Isolation, identification, and biochemical characterization of a novel bifunctional phosphomannomutase/phosphoglucomutase from the metagenome of the brown alga Laminaria digitata - Jackson, Stephen A.; Duan, Maohang; Zhang, Pengyan; Ihua, Maureen W.; Stengel, Dagmar B.; Duan, Delin; Dobson, Alan D. W. (Frontiers in Microbiology, 2022)
Macroalgae host diverse epiphytic bacterial communities with potential symbiotic roles including important roles influencing morphogenesis and growth of the host, nutrient exchange and protection of the host from pathogens. Macroalgal cell wall structures, exudates and intra-cellular environments possess numerous complex and valuable carbohydrates such as cellulose, hemi-cellulose, mannans, alginates, fucoidans and laminarin. Bacterial colonizers of macroalgae are important carbon cyclers, acquiring nutrition from living macroalgae and also from decaying macroalgae. Seaweed epiphytic communities are a rich source of diverse carbohydrate active enzymes which may have useful applications in industrial bioprocessing. With this in mind, we constructed a large insert fosmid clone library from the metagenome of Laminaria digitata (Ochrophyta) in which decay was induced. Subsequent sequencing of a fosmid clone insert revealed the presence of a gene encoding a bifunctional phosphomannomutase (PMM)/phosphoglucomutase (PGM) enzyme 10L6AlgC, closely related to a protein from the halophilic marine bacterium, Cobetia sp. 10L6AlgC was subsequently heterologously expressed in E. coli and biochemically characterized. The enzyme was found to possess both PMM and PGM activity, which had temperature and pH optima of 45 °C and 8.0, respectively; for both activities. The PMM activity had a Km of 2.229 mM and Vmax of 29.35 mM·minˉ¹·mgˉ¹ while the PGM activity had a Km of 0.5314 mM and a Vmax of 644.7 mM minˉ¹·mgˉ¹. Overall characterization of the enzyme including the above parameters as well as the influence of various divalent cations on these activities revealed that 10L6AlgC has a unique biochemical profile when compared to previously characterized PMM/PGM bifunctional enzymes. Thus 10L6AlgC may find utility in enzyme-based production of biochemicals with different potential industrial applications, in which other bacterial PMM/PGMs have previously been used such as in the production of low-calorie sweeteners in the food industry.